The Knowledge About Celiac Disease Among Healthcare Professionals and Patients in Central Europe. Issue 4 (April 2021) - Riznik, Petra; De Leo, Luigina; Dolinsek, Jasmina; Gyimesi, Judit; Klemenak, Martina; Koletzko, Berthold; Koletzko, Sibylle; Koltai, Tunde; Korponay-Szabó, Ilma Rita; Krencnik, Tomaz; Milinovic, Marina; Not, Tarcisio; et al.
ABSTRACT: Objectives: Celiac disease (CD) remains undiagnosed for a long time in many adult and pediatric patients. We assessed the knowledge about CD among healthcare professionals (HCPs) and CD patients in Central Europe (CE). Methods: HCPs and CD patients from 5 CE countries were asked to complete the web-based questionnaire about CD. The questions were divided into subsections on epidemiology, clinical presentation, diagnostics, treatment, and follow-up. Achieved scores of different specialists managing patients with CD were compared and regional differences in patients' knowledge were analyzed. Results: Questionnaire was completed by 1381 HCPs and 2262 CD patients or their caregivers from Croatia, Hungary, Germany, Italy, and Slovenia. Mean score achieved by HCPs was 50.9%, and by CD patients 56.4%. Pediatric gastroenterologists scored the highest (69.4%; P < 0.001). There were significant differences in knowledge of patients from different CE regions with German participants scoring the highest (58.3%). Members of CD societies scored higher compared with nonmembers (mean score 58% vs 53.2%; P < 0.001) and patients diagnosed less than 5 years ago scored higher compared with those diagnosed more than 10 years ago (mean score 57.3% vs 54.6%; P < 0.001). Conclusions: The knowledge about CD among HCPs and CD patients is not satisfactory. Further awareness-raising and learning activities are needed to improve HCPs' knowledge and to minimize the number of unrecognized patients and unnecessary diagnostic delays. Patients should be better informed about their disease to reach higher compliance with the gluten-free diet. Abstract : Supplemental Digital Content is available in the text